Expect nothing fear nothing : the situationist movement in Scandinavia and elsewhere - Rasmussen, Mikkel Bolt; Jakobsen, Jakob (Copenhagen : Nebula, 2011)
This volume is the first English-language presentation of the Scandinavian Situationists and their role in the Situationist movement. The Situationist movement was an international movement of artists, writers and thinkers that in the 1950s and 1960s tried to revolutionize the world through rejecting bourgeois art and critiquing the post-World War Two capitalist consumer society.
"This book gathers presentations from the 'Expect anything fear nothing' conference that took place in Copenhagen in the People's House on 15 and 16 March 2007"
boek